The Role Of Teachers In Improving The Ability To Read The Quran At State Elementary School 8 Jeumpa - Ajamunzalifah, Ajamunzalifah; Saifullah, Saifullah; Murtadha, Murtadha (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the role of teachers in improving Qur'an reading ability at SD Negeri 8 Jeumpa. The ability to read the Qur'an correctly is a crucial aspect of Islamic religious education, yet students face challenges such as limited learning time, varying reading skills, and lack of family support. This qualitative descriptive research collected data through observation, interviews, and documentation. Research subjects included Islamic Religious Education teachers and upper-grade students. Primary data came from teachers and students, while secondary data was sourced from school documents and literature. The study found that teachers play a significant role in enhancing students’ Qur'anic reading, particularly in tajwid, makharijul huruf, adab in recitation, and rules of waqaf and wasal. Strategies such as peer learning, extra guidance, and use of digital media were effectively applied. Students in Grade III showed basic understanding but with pronunciation difficulties, while Grade IV students demonstrated more mastery, though some struggled with waqaf and recitation art. Main obstacles include limited time, ability gaps, and minimal parental support. Solutions implemented involve peer methods, extended learning hours, teacher training, intensive mentoring, small group teaching, and parental involvement, all contributing to improved Qur'an reading proficiency among students.